2022
DOI: 10.1177/2050313x221135595
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of osmotic demyelination syndrome in diabetes mellitus: A case report and literature review of various etiologies for osmotic demyelination syndrome

Abstract: Osmotic demyelination syndrome is a rare condition reported mainly in the case of rapid correction of hyponatremia, but it can occur even in the case of complicated diabetes mellitus either during rapid correction of hyperglycemia or anytime during the complicated diabetes mellitus. We report a case of complicated diabetes mellitus developing osmotic demyelination syndrome. The patient had presented with altered sensorium and seizure, which was initially diagnosed as hyperglycemia, but during his treatment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several case reports have described ODS complications in patients with DKA/HHS ( 9 ). However, unlike these cases, the treatment in the current case was not complicated by acute serum sodium changes, such as an increase of >10 mmol/L/day, including the first 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports have described ODS complications in patients with DKA/HHS ( 9 ). However, unlike these cases, the treatment in the current case was not complicated by acute serum sodium changes, such as an increase of >10 mmol/L/day, including the first 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As no clinical trials exist to guide treatment once ODS has been established, preventing the onset of this syndrome is therefore essential (3).To prevent ODS, a relatively rapid correction (1-2 mmol/L/h for the first 3-4 h and up to 10-12 mmol/L over the first 24 h) is recommended in patients with an altered mental status (8). However, several cases of ODS have been reported in patients with diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar syndrome (HHS) following slow correction of hyponatremia (9,10). Risk factors include severe hyponatremia (<115 mEq/L), alcohol use disorder, hypokalemia, liver disease, and malnutrition (11).…”
Section: Introductionmentioning
confidence: 99%
“…Demyelinating lesions in the pontine white matter tracts are referred to as central pontine myelinolysis (CPM) [1] ,while those involving structures such as the basal ganglia, thalamus and subcortical white matter are known as extrapontine myelinolysis (EPM) [2].A retrospective study in 2015 showed an incidence rate of 2.5% for osmotic demyelination syndrome among patients admitted to the intensive care unit [3].It has been reported that this condition can occur due to various factors such as central diabetes insipidus, posterior pituitary hormone replacement therapy, hyponatremia and hypokalemia from various causes and their rapid correction, liver transplantation, pituitary tumor resection, renal dialysis, pregnancy, high-dose corticosteroid administration and hyperglycemia [4][5][6].SARS-CoV-2 infection may also be a risk factor as it has been associated with various brain injuries, renal injuries and hyponatremia.…”
Section: Introductionmentioning
confidence: 99%
“…This complication has been observed in poorly controlled type 1 and type 2 diabetes, and the clinical presentation can vary widely, with reported symptoms including spastic quadriparesis, dysarthria, ataxia and emotional lability. [4][5][6] Due to the rarity of ODS occurring in chronic hyperglycaemia, there is a paucity of data on the reversibility of symptoms, but case reports suggest that full or significant recovery can be seen within weeks to months with supportive treatment. Interestingly, despite almost full recovery in our patient at 5 months, a follow-up MRI showed persisting pontine abnormalities.…”
mentioning
confidence: 99%
“…The pons is particularly susceptible due to its complex composition of white and grey matter. 6 However, this mechanism does not explain why chronic hyperglycaemia without sudden fluctuations can lead to CPM. It has been proposed that chronic hyperglycaemia and hyperosmolarity may disrupt the bloodbrain barrier, causing plasma leakage and brain oedema.…”
mentioning
confidence: 99%